Обґрунтування періодичності технічного обслуговування агрегатів очищення мастила в двигунах внутрішнього згоряння. - Дашивець, Галина Іванівна; Новік, О. Ю.; Паніна, В. В. (Мелітополь, ТДАТУ, 2019)
UKR :Роботу присвячено дослідженню різних систем очищення мастила в двигунах Д-240: серійна схема; серійна схема, де центрифуга має захисну сітку; комбінована система: серійна центрифуга на повному потоці і паперовий фільтр на відгалуженні. Спостереження велось за двигунами протягом періоду накопичення відкладень агрегатами очищення до повної брудовміскості. Зміна якості мастила проводилось по фізико-хімічним показникам: лужному числу, вмісту механічних домішок, продуктів зносу, кінематичній в'язкості, часу накопичення агрегатами повної грязеємності та щільності осаду. Отримані дані показали, що більші значення терміну напрацювання двигуна до моменту повної брудовміскості, щільності осаду і маси були при експлуатації комбінованої системи очищення, що дозволило використовувати мастило і обслуговувати агрегати очищення з періодичністю, що дорівнює міжсезонному технічному обслуговуванню.////////// ENG: The work is devoted to the study of various systems for cleaning lubricants in engines D-240: serial scheme; centrifuge serial scheme having a protective grid; Combined system: full flow batch centrifuge and paper filter on the branch. It is proved that the deterioration of the physical and chemical parameters of the lubricant during the operation of the engines corresponds to the accumulation of deposits in the rotors of centrifuges. The observation was carried out by the engines D-240 during the period of accumulation of deposits by cleaning units to full dirt. Lubrication samples were selected after a certain period of operation of the engine to detect the dynamics of oil change. At the same time, the control of filling the centrifuge rotors with polluting impurities was carried out by partial disassembly and weighing of the glass after draining of the lubricant from the internal surface of the precipitate. The quality of the lubricant was evaluated according to the physic-chemical parameters: alkaline number, content of mechanical impurities, products of wear, kinematic viscosity, accumulation time of aggregates of full mud capacity and sediment density. Studies have shown that the use of a combined purification system leads to stabilization of the alkaline additive treatment process, which occurs earlier and at a higher level. The content of mechanical impurities and deterioration products using this scheme of purification system is at a lower level compared to serial centrifuges. Summary of article. Larger values of the engine lifetime until the moment of full dirt holding capacity, sediment density and mass, which were during the operation of the combined purification system, will allow the use of lubricant and serve cleaning units with a periodicity equal to inter-season maintenance.
JUSTIFICATION OF THE PERIODICITY OF THE TECHNICAL SERVICE OF OIL CLEANING UNITS IN INTERNAL COMBUSTION ENGINES
Keywords: лужне число; кінематична в'язкість; моторне мастило; система очищення; центрифуга; фізико хімічні показники; вміст механічних домішок; продукти зносу; motor oil; kinematic viscosity; physical and chemical parameters; attrition products; purification system; centrifuge; alkaline number; content of mechanical impurities